Breathing for Two. Issue 1 (23rd March 2022) - Rudder, M.; Russo, M.; Ventetuolo, C.E.
Abstract : ( N Engl J Med . 2021;384:61–68) This feature contained details about one patient's case, with a clinician's commentary interspersed throughout. The case was that of a 29-year-old woman at 26 weeks gestation with undifferentiated connective tissue disease, presenting with cough and shortness of breath.